ANALYSIS OF KNOWLEDGE ABOUT PREGNANCY AND BREASTFEEDING OF MOTHERS AT ASSITED AT CATAN - MACAÉ, RJ. (Fiep Bulletin - online, 2014)
Breastfeeding is the most indicated natural intervention strategy that combined with the practice of timely and adequate complementary feeding, assists in reducing infant mortality. This study aims to describe the knowledge about breastfeeding for pregnant women and mothers assisted at CATAN, Macaé - Rio de Janeiro. A cross-sectional, quantitative study was primarily held at CATAN in Macaé, in April 2013, with pregnant women and mothers of children under 03 years who attended the Municipal Program to Fight Malnutrition - Pregnant women. The selected group was interviewed by scholars PET Health and PIBEX UFRJ, Campus UFRJ – Macaé Professor Aloísio Teixeira, who used a form with 15 closed questions, adapted from the currently form adopted by the General Coordination for Food Policy and Nutrition, Ministry of Health for evaluation of food practices for children under two years. Data was entered and consolidated by using Microsoft Excel 2010. We interviewed 21 pregnant women and mothers of children under three years, representing 53% of the clients assisted by the program. As for knowledge about the definition of exclusive breastfeeding, 76.2% of respondents correctly defined the term. In relation to mixed feeding, 45% were unable to answer correctly. As to knowledge about breastfeeding duration, 42.9% answered that it should be up to 1 year old. We conclude that in general about 45% of the group does not have adequate knowledge on the topic breastfeeding. Training workshops on breastfeeding should be offered to the evaluated group.
Keywords: Infants; Pregnant Women; Healthy Eating